LOYALITAS GURU DITINJAU DARI LINGKUNGAN KERJA, PEMBERDAYAAN GURU, KOMPENSASI, DAN KEPEMIMPINAN KEPALA SEKOLAH DI SDIT MUTIARA INSAN SUKOHARJO - Raharjo, Sigid Budi; Sudarwati, Sudarwati; Istiatin, Istiatin (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
This study aims to examine and evaluate the influence of the work environment on teacher loyalty at SDIT Mutiara Insan Sukoharjo. It also explores the impact of teacher empowerment, compensation, and principal leadership on teacher loyalty at the same institution. The research adopts a descriptive quantitative approach and was conducted at SDIT Mutiara Insan Sukoharjo. A total of 61 teachers participated in the study, with the sampling method using a census technique, meaning the entire population was included as the sample. The collected data were analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination. The findings reveal that the work environment, teacher empowerment, compensation, and leadership each have a significant influence on teacher loyalty at SDIT Mutiara Insan Sukoharjo. These results highlight the important role these factors play in fostering teacher commitment and long-term engagement within the school. Keywords: Teacher Loyalty, Work Environment, Teacher Empowerment, Compensation, Principal Leadership